Nas fronteiras da liberdade: colonização, descolonização e ritos fúnebres na Angola contemporânea - Barbosa, Francisco José (2015)
This thesis is aimed to investigate the history of Angola by approaching the violence and suffering caused by Portuguese colonization and decolonization, and by underlining the arrival of its first inhabitants, particularly regarding the tradition of honoring their ancestors in a heritage of belonging, which has somehow echoed in society nowadays. This study highlights the contentious relationship between the colonizer and the colonized due to disputes over land acquisition, a factor which led to violent conflicts between them, as well as to ongoing violence by Angolan political groups in the post-colonial period, eventually leading to the physical and moral devastation of the country. Thus, it also emphasizes the importance that death rites currently have in Angolan society. The results investigated herein show that the Portuguese metropolis explored and enslaved Angolan people through physical violence and colonial oppression, and later, in the period of decolonization, violence was driven by the pursuit of power, hence culminating in a civil war and in increased social inequality. All the suffering caused to the people was diminished during slavery through death rites driven by suicide, which was regarded as a legitimate way to draw them closer to their ancestors and to help relieve their suffering from the hardships of colonization. However, given the influence of the Catholic Church, the practice of suicide was no longer possible during the civil war, so this method was replaced by the funeral ritual as the main gateway to heaven and also as a way of honoring the ancestors in life. Therefore, the symbolic framework of death rituals is of major importance in society nowadays, as it demonstrates how this practice draws together people of any social level